Investigation of Microsoft Teams and Skype as Distance Education Tools ın Terms of Digital Forensics - Keles, Tugce; Çolak, Yunus Emre; Ilhan, Nurcan; Yıldırım, Kübra; Yıldız, Arif Metehan; Tuncer, Türker; Dogan, Sengul (My University, 2024)
In today's society, the internet has become a ubiquitous necessity due to the widespread use of technology. This necessity has disrupted traditional norms and has affected all aspects of life. Undoubtedly, the education sector is one of the most significant areas affected by technology. As the population rate increases, the importance and necessity of education also increase. In response to this need for education, new educational models emerge based on the contemporary conditions. One of the critical factors that lead to the emergence of these new models is the COVID-19 outbreak that affected the entire world in March 2020. As a result of this epidemic, countries have adopted various methods in the field of education and training. Some countries suspended their educational activities, while others have continued the process through distance education. Distance education is a teaching method that relies heavily on the active use of information and information tools. The extensive use of distance education tools can attract the attention of malicious individuals who may seek to access these services directly or indirectly. This study aims to present the data and information obtained from analyzing the traffic information stored by Microsoft Teams and Skype or incoming and outgoing traffic information over the network in an isolated environment. The study was conducted on computers with the Windows 10 operating system and web client applications installed. One of the primary goals of this study is to assist researchers who will study distance education tools in the future.
Keywords: Distance Eeducation; Microsoft teams; Skype; Wireshark